The Employment of Ukrainians as an Opportunity to Fill the Labour Market in Poland – Selected Issues - Krystyna Gomółka; Małgorzata Gawrycka; Marta Kuc-Czarnecka (Studia Europejskie, 2023)
The labour market in Poland has undergone significant transformations over the past two decades. The observed changes have been influenced by various factors related to, among other things, the possibility of free movement of the population resulting from membership of EU structures, demographic changes, technological changes, and the automation and robotisation of production processes. Demographic change is becoming a significant challenge, highlighting the shortage of workers with different qualifications and competencies in the labour market in various sectors of the national economy. This paper aims to indicate to what extent Ukrainian citizens can fill the gaps in Poland’s emerging labour market. To that end, a survey was conducted in the Qualtrics programme in May-June 2022 among Ukrainian citizens who arrived in Poland before 24th February 2022, i.e., before the outbreak of the war and who were registered in the Gremi Personal database. This particular company provides support connected to employment for Ukrainians. Due to the non-probabilistic sampling technique, the results cannot be generalised with regard to the entire population. To analyse the results, descriptive statistics were used to examine the population structure and determine the signifi cance of the characteristics studied and the correlation between them. The research shows that labour shortages in Poland’s labour market can be compensated to some extent by employing migrants from, for example, Ukraine. The commencement of the proper research was preceded by the preparation of a pilot study and the collection and analysis of statistical data related to the situation on the Polish labour market, taking into account the level and structure of employment and an indication of shortages in the labour market when the research was prepared, and the fact that complete statistical data ended in 2020, hence the decision to include this research period in the analyses.